1995
DOI: 10.1007/bf02254202
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis delivery in children on nightly intermittent and tidal peritoneal dialysis

Abstract: To achieve more adequate dialysis in a shorter treatment time, seven children, characterized as high/high average (H/HA, 5 patients) and low/low average (L/LA, 2 patients) transporters according to the peritoneal equilibration test, were treated with tidal peritoneal dialysis (TPD) for 13.7 +/- 5.7 months, after being treated with nightly intermittent peritoneal dialysis (NIPD) for a similar period. We determined the TPD prescription necessary to provide improved clearances compared with NIPD within the same o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 7 publications
0
10
0
3
Order By: Relevance
“…HDF with a highly permeable membrane is as efficient as HD for low-molecular-weight compounds, but is more efficient than HF for low-molecular-weight compounds [29]. Moreover, HDF, besides its blood purification efficiency, is associated with a lower intradialytic morbidity rate [30, 31], as is HF [3]. On-line HDF [24, 25], in which filtered dialysate free of toxins and pyrogens is used as replacement fluid, enables use of an elevated convection fluid rate, especially in predilution mode, and facilitates a dialysis dose increase without a cost increase.…”
Section: Guideline 5: Principles Of Blood Purificationmentioning
confidence: 99%
“…HDF with a highly permeable membrane is as efficient as HD for low-molecular-weight compounds, but is more efficient than HF for low-molecular-weight compounds [29]. Moreover, HDF, besides its blood purification efficiency, is associated with a lower intradialytic morbidity rate [30, 31], as is HF [3]. On-line HDF [24, 25], in which filtered dialysate free of toxins and pyrogens is used as replacement fluid, enables use of an elevated convection fluid rate, especially in predilution mode, and facilitates a dialysis dose increase without a cost increase.…”
Section: Guideline 5: Principles Of Blood Purificationmentioning
confidence: 99%
“…Patients with a high transporter status can reach adequate solute clearances with nightly TPD, while patients with high-average transport should still additionally benefit from one or more daytime dwells. Studies in pediatric patients showed that TPD was equally or more effective than standard APD but required larger total dialysate volumes, with consequently higher costs [84,131]. Optimization of TPD efficiency can be attained by adapting tidal volume to the drainage profile of each patient, thus reducing the fill and drain dead times [6].…”
Section: Tidal Pdmentioning
confidence: 99%
“…The efficiency of tidal peritoneal dialysis (TPD) is mainly conditioned by total volume of PD fluid delivered and by the individual’s peritoneal transport rate. Patients with high transport rates can reach adequate solute clearances with intermittent nightly TPD, while patients with high average transport rates would benefit from one or more daytime dwells [56, 57]. A further increase of TPD efficiency can be attained by adapting tidal volume to the drainage profile of each patient, thus reducing the fill and drain dead times [58].…”
Section: Prescription For Pd Regimenmentioning
confidence: 99%